Skeletal maturity of children with multiple osteochondromas: Is diminished stature due to a systemic influence?. (October 2015) - Staal, Heleen M.; Goud, Annemarie L.; van der Woude, Henk-Jan; Witlox, Marianne Adhiambo; Ham, S. John; Robben, Simon G. F.; Dremmen, Marjolein H. G.; van Rhijn, Lodewijk W.
Background: Multiple ostechondromas (MO) is an autosomal dominant inherited disease caused by mutated exostosin genes. It mostly affects the long bones and can lead to growth disturbances, especially disproportionate short stature. Both the local effect on growth plates and the systemic influence of the gene disorder on growth mechanisms might explain the diminished stature. Purpose: The hypothesis of this study is that the diminished stature in adults with MO is due to a systemic influence, leading to early skeletal maturation and early closure of the growth plate. Therefore, in these patients the skeletal age in adolescence is hypothesized to be higher than the calendar age. Methods: Radiographs of the left hand were collected from 50 MO-affected children. The skeletal age was calculated using these radiographs according to the Greulich–Pyle bone scale and was compared to the calendar age at the time of radiography. Results: Children aged 3–12 years had a significantly lower skeletal age compared to their calendar age ( p = 0.030). Children aged 12–17 years had a significantly higher skeletal age ( p = 0.019), especially boys. Skeletal maturation in children with MO therefore differs from their peers. Conclusion: In this study, the skeletal age in younger children with MO is lower than their calendar age. For adolescents, particularly boys, this is reversed, suggesting an earlier or faster closure of the growth plates. These findings support a systemic influence of the gene defect on growth rate.